The application of sinusoidal PWM technique on AC-DC converter in improving its input and output performances - 199861 Aw, Keng Leang (Kuala Lumpur : UTM, 1993)
Project paper (Bachelor of Electrical Engineering) - University Teknologi Malaysia, 1993